Failure analysis of a stainless steel component operating inside an acid leaching reactor. (July 2023) - ElJersifi, Adnane; Ben Ali, Meriem; El Maalam, Khadija; Chbihi, Abdelouahed; Aouadi, Khalil; Ouzaouit, Khalid; Naamane, Sanae
Highlights: A failed 316 stainless steel component operating in an acidic environment with high levels of chlorides and sulfides at 90 °C is analyzed. Deviations in carbon and nickel content led to lower resistance to localized corrosion as verified by XRD and SEM analysis. Extensive cracking weakened the component and was found to link multiple CaSO4 inclusions. This acted as the main failure mechanism. Abstract: In this study, we examine the failure of a stainless steel component used for the agitator of the leaching reactor of a hydrometallurgy plant. The sample was subjected to several tests, starting with the characterization of the alloy's chemical composition followed by a study of the working environment and a detailed microscopic observation of the surface and cross-section of the sample. The specifications require the use of a 316L stainless steel which is generally used for its good corrosion resistance due its high Chromium, Molybdenum and Nickel contents in environments containing chlorides such as sea water. The results found, however, that the alloy exhibited higher amounts of carbon than specified and lower amounts of nickel, both of which affected the components corrosion resistance. The analysis of the working environment found high amounts of chlorides and sulfates to the point that even the specified alloy is not corrosion resistant enough, especially at a working temperature of 90 °C. Finally, the microscopic examination led to the root failure mechanisms which are, in this case, the intergranular corrosion which was especially effective in this case where carbon content isn't low enough, and stress corrosion cracking which was accelerated due the multiple CaSO4 inclusions found all around the material. The extensive cracking caused by those inclusions led to the corrosive agents to seep into the material, corroding it further.